The Economic Impact of Banking the Unbanked Evidence From Mexico - Bruhn, Miriam (The World Bank, 2009)
This paper examines the effects of providing financial services to low-income individuals on entrepreneurial activity, employment, and income. The analysis exploits cross-time and cross-municipality variation in the opening of Banco Azteca in Mexico to measure these effects with a difference-in-difference strategy. Banco Azteca opened more than 800 branches simultaneously in 2002, focusing on low-income clients. The results show that the opening of Banco Azteca led to an increase in the number of informal business owners by 7.6 percent. Total employment also increased, by 1.4 percent, and average income went up by about 7 percent